PENGARUH ETIKA UANG (MONEY ETHICS) TERHADAP KECURANGAN PAJAK (TAX EVASION) DENGAN RELIGIUSITAS INTRINSIK DAN MATERIALISME SEBAGAI VARIABEL PEMODERASI - Nuraprianti, Desi; Kurniawan, Asep; Umiyati, Indah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
This study aims to determine (1) the effect of money ethics on tax evasion, (2) to know intrinsic religiosity moderate the effect of money ethics on tax evasion, and (3) to know materialism moderate the effect of money ethics on tax evasion This study uses survey method and population is Individual Taxpayer registered in Tax Office Pratama Subang, sampling technique using incidental sampling technique. The data used consist of primary data, derived from the distribution of questionnaires to Individual Taxpayers registered in the Office of Tax Service Pratama Subang. Analysis of the data used is stepwise regression analysis using SPSS version 22 data processing program. Results from this study are (1) money ethics has a positive effect on tax evasion, (2) intrinsic religiosity does not moderate the effect of money ethics on tax evasion, and (3) materialism does not moderate the effect of money ethics on tax evasion.